A critical analysis of soil (and water) conservation practices in the Ethiopian Highlands: implications for future research and modeling - Fenta, H. M.; Aynalem, D. W.; Malmquist, L.; Haileslassie, Amare; Tilahun, Seifu A.; Barron, Jennie; Adem, Anwar A.; Adimassu, Zenebe; Zimale, Fasikaw A.; Steenhuis, T. S. (Elsevier, 2024)
Soil and water conservation have been traditionally part of farming practices for thousands of years. Despite massive efforts to implement modern soil and water conservation practices (SWCPs) in the Ethiopian Highlands, soil erosion increased after the 1970s when social and political events led to a remarkable change in land use. This review aims to critically analyze the impact of conservation practices on soil loss and crop yield and highlight research and modeling gaps. In doing so, 120 published articles on experimental and simulated soil losses in the Ethiopian Highlands were retrieved from the refereed literature. We found that most published experimental studies evaluating SWCPs lasted less than five years in areas of less than 100 ha. Most modeling studies were over short periods, too; some models simulated soil loss over large areas. The literature analysis for these short-term experimental studies showed that SWCP decreased soil loss on individual sites and increased crop yield in semi-arid regions. Simulated sediment concentration increased as a function of watershed size, while observed soil losses did not follow this trend. Moreover, the decrease in soil loss due to the soil and water conservation practices on small plots was also greatly overestimated. Consequently, past research and current modeling techniques are inconclusive on the effectiveness of SWCPs in large catchments over periods exceeding five years and those with active gullies. Additional long-term experimental studies in catchments are required to evaluate whether SWCPs can decrease sediment loads.